2013
DOI: 10.1177/0003319713504820
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Serum Total Bilirubin Levels and Severity of Coronary Artery Disease in Patients With Non-ST-Segment Elevation Myocardial Infarction

Abstract: We studied 403 consecutive patients with non-ST-segment elevation myocardial infarction (NSTEMI). This population was divided into tertiles according to the SYNTAX score (SXscore). The high SXscore group was defined as an SXscore ≥13, and the low SXscore group as an SXscore <13. The total bilirubin (sTB) and direct bilirubin levels of patients were significantly higher in the high SXscore group (P = .001 and P = .007, respectively). There was a correlation between sTB and SXscore (r = .495; P = .005). On multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 19 publications
2
24
1
1
Order By: Relevance
“…Kuwano et al 21 also reported that patients with higher TB level had lower instent restenosis risk after PCI. In addition, Gul et al 9 and Kaya et al 12 found no association between TB levels and long-term mortality in patients with STEMI or NSTEMI. In the present study, we reported that high levels of TB and DB were risk factors for adverse events in Chinese ACS patients.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Kuwano et al 21 also reported that patients with higher TB level had lower instent restenosis risk after PCI. In addition, Gul et al 9 and Kaya et al 12 found no association between TB levels and long-term mortality in patients with STEMI or NSTEMI. In the present study, we reported that high levels of TB and DB were risk factors for adverse events in Chinese ACS patients.…”
Section: Discussionmentioning
confidence: 95%
“…Evidence suggested that SYNTAX score, which has been shown to predict major adverse events in patients with coronary heart disease, 20 was positively associated with TB in both STEMI and NSTEMI patients. 12,13 Celik et al 11 and Gul et al 9 demonstrated that high TB level was associated with PCI no-reflow as well as increased in-hospital MACE in patients with STEMI. On the contrary, Kim et al 8 found a negative correlation of TB levels and long-term outcomes in patients who underwent PCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SYN-TAX score (SXscore) is an anatomic scoring system which quantifies the properties of a lesion including complexity, morphology, and location in the coronary vasculature. 5) It has been shown that the SXscore may predict short and long-term mortality in patients with CAD intervention. 6) The role of inflammation in the initiation and progression of coronary atherosclerosis is well described.…”
Section: N On-st Segment Elevation Myocardial Infarctionmentioning
confidence: 99%
“…20 Increased serum TB was independently associated with severity of CAD on SYNTAX score in patients with NSTEMI. 21 Such an association between higher serum TB and higher SYNTAX score was also found in patients with STEMI. 22 Increasing TB was significantly associated with the risk of pump failure death but not for sudden death in patients with severe systolic heart failure.…”
Section: Discussionmentioning
confidence: 77%